The Link Among Trade, Fdi and Immigration - Černoša, Stanislav (Naše gospodarstvo/Our economy, 2014)
Using the gravity model, this paper provides a new empirical framework that analyzes the importance of the link among trade, FDI, and immigration. A further significant contribution of this analysis is the appropriate handling of a large num- ber of zeroes in migration statistics. In this way, the unbalanced panel database of the 15 core European member states (EU15) as destination countries is formed. The results of the estimation show that the introduced explanatory variables, such as the common language, destination country’s population, and great circle distance between two countries, represent the most significant deterministic factors that ge- nerally explain the share of the immigrant population. It is also confirmed that the sending country’s population, trade, FDI, and sending country’s landlocked position are important determinants positively influencing the share of immigration.
Keywords: Trade; foreign direct investments; international migration; gravity model